2017
DOI: 10.1186/s12966-017-0476-0
|View full text |Cite
|
Sign up to set email alerts
|

The combined impact of diet, physical activity, sleep and screen time on academic achievement: a prospective study of elementary school students in Nova Scotia, Canada

Abstract: BackgroundFew studies have investigated the independent associations of lifestyle behaviors (diet, physical activity, sleep, and screen time) and body weight status with academic achievement. Even fewer have investigated the combined effect of these behaviors on academic achievement. We hypothesize that the combined effect of these behaviors will have a higher impact on academic achievement than any behavior alone, or that of body weight status.MethodsIn 2011, 4253 grade 5 (10–11 years old) students and their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
104
1
11

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(124 citation statements)
references
References 55 publications
8
104
1
11
Order By: Relevance
“…Furthermore, the findings in the present study are mostly in line with results from a previous 1-year prospective study [42]. In that study, the authors examined if a combination of lifestyle habits, including screen time as well as eating and sleeping habits, could impact academic performance of 4253 elementary students from 10 and 11 years old [42]. They concluded that adherence to screen time as well as eating and sleeping recommendations increase the likelihood of having a better academic performance in mathematics, reading and writing.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Furthermore, the findings in the present study are mostly in line with results from a previous 1-year prospective study [42]. In that study, the authors examined if a combination of lifestyle habits, including screen time as well as eating and sleeping habits, could impact academic performance of 4253 elementary students from 10 and 11 years old [42]. They concluded that adherence to screen time as well as eating and sleeping recommendations increase the likelihood of having a better academic performance in mathematics, reading and writing.…”
Section: Discussionsupporting
confidence: 93%
“…They concluded that adherence to screen time as well as eating and sleeping recommendations increase the likelihood of having a better academic performance in mathematics, reading and writing. Also, they reported that adherence to multiple healthy lifestyle recommendations have an additive effect on the associations with academic performance [42]. In contrast, results of a 2-year longitudinal study conducted in the United Kingdom in 11014 children indicated that screen time at 5 years old did not predict variations in attention capacity 2 years later [57].…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…A British birth cohort study (N = 12,537) indicates that adolescent obesity (at age 16 years) is associated with fewer years of schooling and predicts lower income in young women (at age 23 years), including those who are no longer obese (Sargent 1994). These findings were further confirmed by Han 2011, using the National Longitudinal Survey of Youth 1979 (N = 1974, follow-up 12 to 16 years), and by Sabia 2012, using the National Longitudinal Study of Adolescent Health (N = 12,445, follow-up 13 years) in the USA. Findings from the National Longitudinal Survey of Youth 1997 in the USA (N = 8427, follow-up eight years) suggest that obese adolescents had a 39% lower chance of obtaining a college degree than peers of normal weight (Fowler-Brown 2010).…”
Section: Introductionmentioning
confidence: 73%
“…Few studies have investigated the independent associations of lifestyle behaviors like; diet, physical activity, and body weight status with academic achievement. Even fewer have investigated the combined effect of these behaviors on 5 academic achievement. There has been no study on this issue in Bangladesh to focus on medical students' diet and body weight status and their relationship with the results of professional examinations and class attendance.…”
Section: Introductionmentioning
confidence: 99%